Role of host-encoded proteins in restriction of retroviral integration - Suzuki, Yasutsugu; Chew, Mun Lok; Suzuki, Youichi (Frontiers in Microbiology, 2012)
In retroviral infections, a copy of the viral DNA is first synthesized from genomic RNA by reverse transcription and subsequently integrated into host chromatin. This integration step, executed by the viral enzyme integrase (IN), is one of the hallmarks of retroviral infection. Although an obligate role for IN in retroviral integration has been clearly defined by numerous biochemical analysis of its recombinant protein and genetic analysis of the viral IN gene, several host cellular proteins have also been implicated as key factors involved in the integration step during viral replication. Studies on integration cofactors have mostly emphasized factors that aid the integration process, either through direct or indirect association with IN. However, as in the case of well-known restriction factors such as APOBEC3G, TRIM5α, and tetherin, it has become apparent that host cells may also harbor proteins that act as inhibitors of retroviral integration, particularly HIV-1 integration. Intriguingly, some of these inhibitory proteins appear to hamper the integration process via posttranslational modifications of the components of the preintegration complex, including IN. A better understanding of the molecular mechanisms leading to the inhibition of integration will provide us with clues for the development of new strategies for treating retroviral infections. In this review, we draw attention to recent insights regarding potential host cellular factors that restrict integration, and discuss how these inhibitory effects are achieved.